2004
DOI: 10.1111/j.1582-4934.2004.tb00260.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐atherosclerotic effects of vitamin E – myth or reality?

Abstract: Atherosclerosis and its complications such as coronary heart disease, myocardial infarction and stroke are the leading causes of death in the developed world. High blood pressure, diabetes, smoking and a diet high in cholesterol and lipids clearly increase the likelihood of premature atherosclerosis, albeit other factors, such as the individual genetic makeup, may play an additional role. Several epidemiological studies and intervention trials have been performed with vitamin E, and some of them showed that it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0
7

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(92 citation statements)
references
References 133 publications
0
85
0
7
Order By: Relevance
“…It has a chromanic nucleus, with an aliphatic side chain which can protect lipid structures from peroxidation (Munteanu et al, 2004). In addition, it has also been reported that α-tocopherol inhibits NADPH oxidase by suppressing PKC-mediated phosphorylation and translocation of p47-phox (Cachia et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…It has a chromanic nucleus, with an aliphatic side chain which can protect lipid structures from peroxidation (Munteanu et al, 2004). In addition, it has also been reported that α-tocopherol inhibits NADPH oxidase by suppressing PKC-mediated phosphorylation and translocation of p47-phox (Cachia et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular players in signaling expected to be influenced by the interaction between these proteins and vitamin E are numerous (reviewed in [4][5][6][7]) and include kinases such as PKC, Akt/PKB, some members of MAPK family and cell cycle related kinases, and the recently proposed downstream components of the death domain and proteins of the endoplasmic reticulum stress signaling [8]. Tocotrienols have been reported to be ligands of the estrogen receptor b (ERb) [9] that could thus contribute some aspects of vitamin E signaling that will be further discussed later in the section dedicated to tocotrienols.…”
Section: Cellular Effects and Signaling Of Vitamin Ementioning
confidence: 99%
“…em pessoas fumantes ou que consumam quantidade elevada de PUFAs 36 . A partir destes resultados contraditórios, estudos in vitro têm demonstrado que em doses elevadas o α-tocoferol pode agir como pró-oxidante, caso não haja concentrações equivalentes de outros antioxidantes para regenerar o radical α-tocoferila a α-tocoferol 25 .…”
Section: Figura 5 Etapas Da Lipoperoxidação E Ação Antioxidante Do αunclassified
“…A vitamina E atua em nível celular, inibindo a proliferação de células musculares lisas das artérias, a agregação plaquetária, a adesão de monócitos à parede do endotélio, a captação de LDL oxidada e a produção de citocinas. Estes mecanismos parecem estar relacionados com efeitos específicos do α-tocoferol na transdução de sinais e expressão gênica 25,37 .…”
Section: Figura 5 Etapas Da Lipoperoxidação E Ação Antioxidante Do αunclassified